THE CAUSAL LINK BETWEEN VACCINATION ADJUVANTS AND AUTISM - Prevenslik, Thomas (International Journal of Research -GRANTHAALAYAH, 2019)
Adjuvants essential in vaccines to stimulate activation of the immune system comprise submicron (< 100 nm) nanoparticles (NPs) of aluminum hydroxide that upon vaccine injection cross the blood-brain-barrier (BBB) and because of their low solubility may remain in the brain for an extended time. Despite over a century of use, the mechanism underlying the stimulation of the immune system by adjuvants has not been understood. Solar UV can optically stimulate most immune systems in the skin, but solar UV is not available inside the brain. By the process of simple QED, the NPs lacking heat capacity by the Planck law conserve heat from brain tissue by emitting UV radiation instead of increasing in temperature. Hence, the causal link between vaccination adjuvants and autism is UV stimulation of the immune system from constituent NPs that cross the BBB. But the UV also damages the DNA of brain tissue and increases the pro-inflammatory interleukin (IL-6) cytokine levels common in autism patients. Pre-vaccination enzyme-linked immunosorbent assay (ELISA) tests of IL-6 level including UV blood irradiation (UBI common in immune-modulating therapy are suggested to determine if a patient will have an adverse vaccination response. Patients having high IL-6 levels are not recommended for vaccination.